O comportamento adaptativo organizacional da indústria da construção civil: estudo de multicaso. - Cortez, Alexandre Schmidt (2004)
The organizational strategic adaptation stopped to be an idiom in order to become a question of success and surviving for companies awaking interests on its discussion in a relevant way in the academic and business environment. This dissertation aimed to study the adaptable organizational behavior of three organizations of industries from civil construction edification sector from Santa Maria, Rio Grande do Sul state, between 1981 and 2003. The characteristics of the strategic types used in the organizations were identified according to the perception of the dominant coalition, in agreement with Miles & Snow model (1978). It is a matter of a multi-case study, in a qualitative approach (Triviños, 1987) that rescued the organization s historic data, defining its critic events and characterizing the strategic periods through the methodology of Miles & Huberman (1984) as well as the methodology of Mintzberg & McHugh (1985). After the definition of the strategic periods, a theoretical analysis that identified the process of strategic adaptation according to the mutant conditions in the organization environment was done characterizing the strategic behavior defensive, prospective, analytical and reactive from the three studied organizations. A contextual, processing and longitudinal research based on the methodological procedures from Direct Research and Grounded Theory was developed simultaneously. Finally, one can conclude that in the studied organizations, the influence of mimetic isomorphism is detached and the majority of the developed strategies occurred through the emergent strategies. Besides that, a strong enterprising spirit of the dominant coalition with the business control centralized on it and with a simple organizational structure was demonstrated.